2019
DOI: 10.1177/2399808318825273
|View full text |Cite
|
Sign up to set email alerts
|

Discretion versus prescription: Assessing the spatial impact of design regulations in apartments in Australia

Abstract: The Victorian Government introduced the Better Apartment Design Guidelines in 2017. The introduction of these new regulations is a response to growing criticism over the quality of the large number of apartments recently constructed in Melbourne. This concern is shared in other Australian cities, but until now Victorian planning regulations have been the least prescriptive and most permissive in terms of apartment design parameters of any Australian jurisdiction. Reflecting on these concerns raises several que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…First, literature has generally uncritically provided a synthesis of policies and tools to shape vertical neighbourhoods with a lack of analysis of their efficiency in meeting a set of outcomes. Second, this literature has narrowly focused on issues linked to strategic heritage protection (Cohen, 1999;Tavernor, 2007) and townscape conservation (Phelps et al, 2002), overlooking how other aspects of high-rise design are planned (or not), such as the quality of internal units (Allouf et al, 2020) or the relationship of high-rise buildings with the public realm (Al-Kodmany, 2017). This article provides an analytical framework to investigate the efficiency of different planning tools in meeting certain outcomes, at different scales of high-rise vertical neighbourhoods, and in a particular political and planning context.…”
Section: A Multi-scalar and Multi-level Governance Critical Explorati...mentioning
confidence: 99%
“…First, literature has generally uncritically provided a synthesis of policies and tools to shape vertical neighbourhoods with a lack of analysis of their efficiency in meeting a set of outcomes. Second, this literature has narrowly focused on issues linked to strategic heritage protection (Cohen, 1999;Tavernor, 2007) and townscape conservation (Phelps et al, 2002), overlooking how other aspects of high-rise design are planned (or not), such as the quality of internal units (Allouf et al, 2020) or the relationship of high-rise buildings with the public realm (Al-Kodmany, 2017). This article provides an analytical framework to investigate the efficiency of different planning tools in meeting certain outcomes, at different scales of high-rise vertical neighbourhoods, and in a particular political and planning context.…”
Section: A Multi-scalar and Multi-level Governance Critical Explorati...mentioning
confidence: 99%
“…Indeed, an evaluation of the implementation of the quantifiable SEPP65 policy requirements in Sydney (NSW) buildings that were developed under the policy found that, on average, buildings were implementing just 56% of the measured requirements ( Foster et al, 2022 ). While compliance was lower than anticipated, studies also underscored the important role that a more comprehensive policy plays in shaping the built form ( Allouf et al, 2020 ; Foster et al, 2022 ). For example, a multi-city study compared Sydney buildings (built under SEPP65) against buildings in Perth (WA) and Melbourne (VIC) that pre-dated the new design legislation in those states and found Sydney buildings implemented significantly more minimum requirements than buildings in other cities ( Foster et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This highlights the generic nature of much of the evidence and its disconnection from the policy environment, practices and legislation ( Allender et al, 2009 ; Durand et al, 2011 ). In contrast, several recent studies have objectively assessed apartment buildings for their adherence with design standards, but these policy-specific measures have not, to date, been assessed in relation to residents perceptions of apartment living and/or health outcomes to evaluate their impact ( Abidi & Rajagopalan, 2020 ; Allouf et al, 2020 ; Foster et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%